The Scrum Culture - Maximini, Dominik (Springer, 2015)
This book is a guide for managers, Scrum Masters and agile coaches who are interested in agile organizational methods and who are planning to introduce Scrum at their own company. Scrum is not only a product development framework but can also be used to structure activities for agile and lean organizational development.